2020
DOI: 10.1002/cctc.202000415
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a Key Synthon of Indole Alkaloid Synthesis by Palladium(II)‐Catalyzed Indole 2‐Methylenephosphorylation

Abstract: A palladium‐catalyzed Catellani‐type reaction of indole with diethyl (iodomethyl)phosphonate has been developed. This new protocol provides an efficient and concise route to 2‐methylene phosphonate indoles, which are key synthons for the construction of indole alkaloids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 111 publications
0
3
0
Order By: Relevance
“…Under the traditional synthetic technology in the conventional reactor, the molar ratio of raw materials (phosphite ester and HCHO) ranged from 1:1.0 to 1:1.3, reaction temperature ranged from 100 C to 120 C, reaction pressure ranged from 3 kPa to 5 kPa, and reaction time ranged from 1h to 5 h. [12][13][14] Because the reaction was extremely exothermic, the targeted HPs exhibited significantly increased byproducts with high acid value (AN), in turn, led to low purity and low yield. [15][16][17][18][19] Stowell et al 20 studied the preparation of HPs with paraformaldehyde and dialkyl phosphite/trialkyl phosphite as raw materials in the presence of triethylamine catalyst. The results indicated that the products showed high AN in the range of 2.6 mg KOH g -1 and 3.5 mg KOH g -1 .…”
Section: Hydroxymethylmentioning
confidence: 99%
“…Under the traditional synthetic technology in the conventional reactor, the molar ratio of raw materials (phosphite ester and HCHO) ranged from 1:1.0 to 1:1.3, reaction temperature ranged from 100 C to 120 C, reaction pressure ranged from 3 kPa to 5 kPa, and reaction time ranged from 1h to 5 h. [12][13][14] Because the reaction was extremely exothermic, the targeted HPs exhibited significantly increased byproducts with high acid value (AN), in turn, led to low purity and low yield. [15][16][17][18][19] Stowell et al 20 studied the preparation of HPs with paraformaldehyde and dialkyl phosphite/trialkyl phosphite as raw materials in the presence of triethylamine catalyst. The results indicated that the products showed high AN in the range of 2.6 mg KOH g -1 and 3.5 mg KOH g -1 .…”
Section: Hydroxymethylmentioning
confidence: 99%
“…[196] Noteworthy, the process was also further extended to both the C2-selective trifluoroethylation of indoles provided that β-diketone ligands are used, [197] and to the synthesis of phosphonate-substituted indoles when using (iodomethyl)phosphonates as coupling partners. [198] Supported by mechanistic investigations and since N-methyl-indole proved to be unreactive while C3-substituted substrates were properly alkylated, the mechanism of this transformation was suggested to proceed through the general catalytic cycle depicted in Scheme 110. [194b] The latter starts with a N-palladation of the indole or pyrrole from a Pd(II) catalyst prior to coordination of the norbornene transient mediator, whose insertion subsequently occurs to afford the corresponding palladium(II) species -that could be isolated and characterized by XRD -before the irreversible C2À H activation and further oxidative addition into the halide coupling partner, thus delivering the corresponding palladium(IV) species.…”
Section: Norbornene-mediated Functionalization Of Indoles and Pyrrolesmentioning
confidence: 99%
“…4 Among them, allylphosphine oxide compounds are attractive molecular structures with broad applications in drug discovery, since they serve as key structural units in some bioactive molecules (Scheme 1a). 5 Hence, the development of de novo synthesis of allylphosphoxy compounds or introducing the corresponding moieties into bioactive molecules is of great significance.…”
mentioning
confidence: 99%